Development of Gas-Separation Membrane-Assisted Lead-Acid Battery - Ismail, A. F.; Hafiz, W. A. (Elsevier B.V., 2005)
The objective of this study is to improve the design of a starting, lighting and ignition (SLI) lead-acid battery with the introduction of gasseparation membrane technology that functions as an electrolyte retainer. Asymmetric polysulfone gas-separation flat-sheet membranes were applied on the battery vent holes that is charged at 15A and the electrolyte loss data were monitored and compared to the conventional battery. Effects of polymer concentration and casting shear rate were investigated in order to produce the most suitable gas-separation membrane, which features minimal electrolyte losses during the charging test. At room temperature, the electrolyte losses of a membrane-assisted leadacid battery are about 6.67 g h-1, while for a conventional battery it is about 26.67 g h-1. During the charging process at a temperature of about 80 ?C, the membrane-assisted lead-acid battery can save up to 40% of electrolyte losses compared to the conventional battery.